Effect of polymer infiltration on structure and properties of carbon nanotube yarns. (July 2015) - Jung, Yeonsu; Kim, Taehoon; Park, Chong Rae
Abstract: Polymer-infiltrated carbon nanotube yarns (CNTYs) were prepared to enhance the mechanical and electrical properties of CNTYs through physical interactions. This work additionally explored the role of the polymer in altering the structures of the CNTYs. The reticulate structures of the CNTYs produced through aerogel methods were infiltrated with a dilute (0.05 wt%) solution of polystyrene (PS), polyacrylonitrile (PAN), or polyvinyl alcohol (PVA), and the structures were characterized. The performances of the CNTYs were closely related to the junction strength and the bundle size in the reticulate CNTYs. Among the three polymers examined, infiltration of PVA—the polymer with the poorest affinity toward CNTs—yielded the greatest improvement in the mechanical and electrical properties of the CNTY. The CNTY deformation properties at each stage of the stress–strain curves could be explained based on the effects of the polymer infiltration on the structure and properties of the CNTY. The results indicated that the specific stiffness, specific strength, toughness, and electrical conductivity are significantly influenced by the molecular-level coupling between the polymer, the CNTs, and the internal structure of the CNTY.